Exchange rate misalignment in Pakistan and its general equilibrium distributional implications - Debowicz, Darío; Saeed, Wajiha (International Food Policy Research Institute, 2014)
Recent findings in the growth literature suggest that developing countries need to keep a devalued exchange rate to stimulate their economic growth. Building on these findings, we econometrically evaluate to what ex-tent the real exchange rate of Pakistan has been aligned with its economic fundamentals, and find that the Pa-kistan rupee has been significantly and systematically overvalued during the last years. We then simulate the general equilibrium effects of an eventual re-alignment of the real exchange rate with economic fundamen-tals, and find not only an expected increase in the relative size of the tradable sector - where productivity in-creases tend to be faster – but also an associated improvement in the income of the poorest groups.